2023
DOI: 10.1108/gm-06-2022-0215
|View full text |Cite
|
Sign up to set email alerts
|

Gender of firm leadership, audit committee gender diversity and audit quality through the lens of audit fee: a Ghanaian insight

Peter Kodjo Luh

Abstract: Purpose This study aims to examine how woman leadership (i.e., woman board chairperson, woman chief executive officer (CEO) and board gender diversity) affects audit fee and also ascertained the interactive effect of woman leadership and gender diversity on audit committee on audit fee. Design/methodology/approach The study applied ordinary least square and fixed-effect estimators on the data of 21 universal banks in Ghana for the period 2010–2021 to estimate the empirical results. Findings It is revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Following the narrative above, there have been extensive empirical research to provide insight on how women in leadership and gender diversity on boards is linked with issues such as cost of capital (Sarang et al , 2022), earnings management (Anh and Khuong, 2022; Mensah and Onumah, 2023), firm profitability (Luh and Kusi, 2023), intellectual capital efficiency (Sanyaolu et al , 2022), audit fee (Garcia-Blandon et al , 2023; Luh, 2024), audit quality (Saidu and Aifuwa, 2020; Koh et al , 2022) and firm stability/risk (Sattar et al , 2022; Menicucci and Paolucci, 2022a). In overall terms, what these studies have revealed is that gender diversity on boards and top executive management has implications for various organizational outcomes, which includes both financial and non-financial outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Following the narrative above, there have been extensive empirical research to provide insight on how women in leadership and gender diversity on boards is linked with issues such as cost of capital (Sarang et al , 2022), earnings management (Anh and Khuong, 2022; Mensah and Onumah, 2023), firm profitability (Luh and Kusi, 2023), intellectual capital efficiency (Sanyaolu et al , 2022), audit fee (Garcia-Blandon et al , 2023; Luh, 2024), audit quality (Saidu and Aifuwa, 2020; Koh et al , 2022) and firm stability/risk (Sattar et al , 2022; Menicucci and Paolucci, 2022a). In overall terms, what these studies have revealed is that gender diversity on boards and top executive management has implications for various organizational outcomes, which includes both financial and non-financial outcomes.…”
Section: Introductionmentioning
confidence: 99%